Qui sont les francophones ? Analyse des définitions selon les variables du recensement de 2001 - Forgues, Éric; Landry, Rodrigue; Boudreau, Jonathan (Institut canadien de recherche sur les minorités linguistiques et Consortium national de formation en santé, 2009)

Utilisation des services gouvernementaux de langue française. Une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités linguistiques, 2009)

Liminaire: Les enjeux reliés à la santé des communautés francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue (Francophonies d’Amérique, 2009)

Capital social, santé et minorités francophones - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Revue canadienne de santé publique / Canadian Journal of Public Health, 2006)

L’environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, Anne; Langlois, André; Landry, Rodrigue; Aunger, Edmund (Francophonies d'Amérique, 2005)

Social capital, health and Francophone minorities - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Canadian Journal of Public Health / Revue canadienne de santé publique, 2006)
The goal of this article is to outline the analytical perspectives of the concept of social capital regarding health and health management. Social capital, as defined in terms of social networks and resources, has a positive impact on a number of areas, notably the health, well-being, and social and economic development of communities. It is also a useful tool for implementing social policy, especially for marginal populations, the elderly, social assistance payments, etc. An action strategy based on the support and development of networks is the key to achieving the social development, health, and well-being of populations. The social ties promoted by these networks provide people with social, cognitive, and emotional support. This has a direct impact on their self-esteem and sense of personal achievement. They also facilitate access to social resources, including social advancement opportunities. In this paper, we examine the vitality, determinants of health, and health management of Canada’s minority Francophone communities.